Enemies of Hope - Tallis, R. author. aut Link
XV, 499 p.
Keywords: Perceptive, passionate and often controversial, Raymond Tallis's latest debunking of Kulturkritik delves into a host of ethical and philosophical issues central to contemporary thought, raising questions we cannot afford to ignore. After reading Enemies of Hope , those minded to misrepresent mankind in ways that are almost routine amongst humanist intellectuals may be inclined to think twice. By clearing away the 'hysterical humanism' of the present century Enemies of Hope frees us to start thinking constructively about the way forward for humanity in the next.